The Nigerian Elite and State Creation: The Creation of False Ethnic Dichotomies for Self Aggradizement (Global Journal of Human-Social Science, 2016)
Nigeria has undergone a long process of restructuring in terms of the number of geopolitical administrative units that constitute the polity. The process is popularly referred to as "state creation" in federal systems, particularly in Nigeria. This study examines the various rationale posited for creation of states in the country, such as quest for balanced federation, integration and fostering a feeling of belonging among its disparate population, national development etc. and finds out that most states created so far in the country were a product of false ethnic dichotomies orchestrated by the ethnic elites through superficial ethnic affiliations. The study concludes that the state creation exercise in the country had benefitted the elite rather than the masses because of the patronages that accrue to the former to the disadvantage of the latter.
Keywords: elite; ethnicity; state creation; federalism; integration